Internalisasi Nilai Karakter Qur’ani melalui Program G7KAIH di Madrasah Ibtidaiyah - Haidar Hafiedz; Fathul Jannah; Nur Kholik Afandi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2026)
The rapid development of technology and globalization poses significant challenges to shaping students’ character, underscoring the need to strengthen Qur’anic-based character education through contextual and sustainable approaches. This study aims to analyze the process of internalizing Qur’anic character values through the Seven Habits of Outstanding Indonesian Children (G7KAIH) program at MI Negeri 1 Samarinda and to identify its supporting and inhibiting factors. This research employs a qualitative field research approach, including participatory observation, semi-structured interviews, and documentation, with eight purposively selected informants. Data were analyzed using the interactive model of Miles and Huberman, supported by triangulation techniques to ensure validity. The findings reveal that the internalization process occurs through three stages: transformation, transaction, and transinternalization, which are integrated into habituation activities, teacher role modeling, and support from both school and family environments. The program contributes to improved discipline, independence, and religious awareness among students. Its success is supported by active teacher involvement, a conducive school environment, and parental participation, while challenges include diverse family backgrounds and limited supervision outside school. Therefore, the G7KAIH program is an effective model for internalizing Qur’anic character values through sustained habituation.